Variation in human T lymphotropic virus III (HTLV-III) antibodies in homosexual men: decline before onset of illness related to acquired immune deficiency syndrome (AIDS). Issue 6501 (12th October 1985) - Biggar, R J; Melbye, M; Ebbesen, P; Alexander, S; Nielsen, J O; Sarin, P; Faber, V
Abstract : Western blot analysis was used to document the development and changes in human T lymphotropic virus III (HTLV-III) antibody among Danish homosexual men followed longitudinally over three years. Reactivity against p15, p24, and p55 appeared earliest. After seroconversion the antibody concentration fluctuated, but in one instance a steady decline in banding intensity was seen during the 18 months before onset of the acquired immune deficiency syndrome (AIDS) and throughout the remaining eight months of his life.